Coupling and coordinated development of environmental regulation and the upgrading of industrial structure: Evidence from China's 10 major urban agglomerations - Xiaozhou Zheng; Renming Liu; Huiping Wang (Economies, 2024)
Exploring the coupling and coordinated development of formal and informal environmental regulation, as well as their impact on the upgrading of the industrial structure of urban agglomerations, represents a new breakthrough. The comprehensive index of formal environmental regulation, informal environmental regulation, and industrial structure upgrading is calculated using the entropy method based on sample data from 127 cities in China's ten major urban agglomerations between 2003 and 2019. The characteristics of the coupling and coordinated development between formal and informal environmental regulation in these urban agglomerations are examined using a coupling coordination degree model. Furthermore, the effects of the coupling and coordinated development of formal and informal environmental regulation on the industrial structure upgrading in urban agglomerations are analyzed through fixed-effect and threshold regression models. The findings demonstrate that although the development of urban agglomerations remains unbalanced, the overall coupling coordination degree between formal and informal environmental regulation is increasing. Generally, the ten major urban agglomerations have transitioned from a state of reluctance coordination to primary coordination. The Pearl River Delta urban agglomerations have progressed from reluctance coordination to middle coordination, while the Yangtze River Delta, Shandong Peninsula, Central Plains, and Beijing-Tianjin-Hebei urban agglomerations have advanced from reluctance coordination to primary coordination. The remaining five urban agglomerations have shifted from near disorder to reluctance coordination. The coupling and coordinated development of formal and informal environmental regulation significantly promote the upgrading of the industrial structure in both overall and grouped samples of urban agglomerations, and the higher the degree of coupling coordination, the greater the promoting effect. Moreover, when informal environmental regulation is considered as a threshold variable, the coupling coordination degree exhibits a broken-line relationship with the industrial structure upgrading in urban agglomerations. Currently, the intensity of informal environmental regulations is relatively reasonable in China's ten major urban agglomerations, and the coordinated development of formal and informal environmental regulations has an impact on the industrial structure of urban agglomerations. Finally, this paper proposes corresponding suggestions encompassing the construction of an environmental regulation policy system, differentiated industrial policy, and the coordinated promotion of various policies.
Keywords: 330; coupling and coordinated development; environmental regulation; panel data; panel threshold regression models; upgrading of industrial structure; urban agglomerations